The risks of opioid treatment: Perspectives of primary care practitioners and patients from safety-net clinics. Issue 2 (3rd April 2017) - Hurstak, Emily E.; Kushel, Margot; Chang, Jamie; Ceasar, Rachel; Zamora, Kara; Miaskowski, Christine; Knight, Kelly
ABSTRACT: Background : Patients with a history of substance use are more likely than those without substance use to experience chronic noncancer pain (CNCP), to be prescribed opioids, and to experience opioid misuse or overdose. Primary care practitioners (PCPs) in safety-net settings care for low-income patients with CNCP and substance use, usually without specialist consultation. To inform communication related to opioid risk, we explored PCPs' and patients' perceptions of the risks of chronic opioid therapy. Methods : We conducted semistructured interviews with 23 PCPs and 46 of their patients, who had a history of CNCP and substance use. We recruited from 6 safety-net health care settings in the San Francisco Bay Area. We transcribed interviews verbatim and analyzed transcripts using grounded theory methodology. Results : (1) PCPs feared harming patients and the community by opioid prescribing. PCPs emphasized fear of opioid overdose. (2) Patients did not highlight concerns about the adverse health consequences of opioids, except for addiction. (3) Both patients and PCPs were concerned about PCPs' medicolegal risks related to opioid prescribing. (4) Patients reported feeling stigmatized by policies aimed at reducing opioid misuse. Conclusion : We identified differences in how clinicians and patients perceive opioid risk. To improve the informed consent process for opioid therapy, patients and PCPs need to have a shared understanding of the risks of opioids and engage in discussions that promote patient autonomy and safety. As clinics implement opioid prescribing policies, clinicians must develop effective communication strategies in order to educate patients about opioid risks and decrease patients' experiences of stigma and discrimination.